Design and Development of InfoRef using Dialogflow: A 24/7 Online Reference Service Platform - Priya; Shivarama Rao, K. (Journal of Information and Knowledge, 2023)
The present study proposes an AI-based conversational agent named InfoRef to provide reference services by creating an interactive interface between library services and users. The application works on the AAA (Anytime, Anywhere, Anyone) model and routes the users to the available information. It provides access to 24/7 information to users. The free version of Dialogflow (a natural language understanding engine by Google) was used for building the InfoRef application. After its development, the InfoRef was integrated with different online platforms like the website, Koha ILS, and Telegram. The integration worked well and generated a similar response on all platforms.